Economic resilience and pandemic response - Rzepka, Agnieszka; Paździor, Artur; Prachowski, Jakub (Routledge, 2025)
"The Covid-19 pandemic upended our social and economic lives. Lockdowns forced firms to implement health and safety protocols, employees to work from home, and businesses of all sorts to close. Even as lockdowns eased, the landscape of work, commerce, leisure and education was irrevocably transformed. While in many ways life has returned to normal, many of the changes wrought by the pandemic are here to stay. This book presents research on these transformations, examining how the economy and society were impacted. Organizing different aspects of the pandemic into individual chapters, the book examines issues such as financing structures, liquidity, profitmaking, investment, financial security, and market valuation, among other topics. Reflecting deep research as well as an extensive review of the literature, each chapter provides not just theoretical and empirical insight but also a set of policy recommendations to insure against similar crises in the future. Encompassing a range of case studies, it outlines strategies for dealing with the manifold challenges of today's business environment. The book showcases the development of particular sectors over the course of the pandemic, and as such, serves as a valuable study, enabling a comprehensive analysis of topics ranging from economics to social dynamics. It provides a deep understanding of this unique period's wide-ranging challenges and transformations and underscores the central economic concern of the pandemic's effect on economic security, a topic discussed throughout several chapters. Furthermore, it includes a discussion on the broader scope of "polycrisis". This volume was designed to appeal to a wide range of readers interested in economics, management, regional studies, and related fields"-- Provided by publisher.
Keywords: Economic history -- 21st century.; Social history -- 21st century.; COVID-19 Pandemic, 2020- -- Influence.; elektronické knihy; electronic books